2012
DOI: 10.3347/kjp.2012.50.4.385
|View full text |Cite
|
Sign up to set email alerts
|

Trichinella spiralis Infection Suppressed Gut Inflammation with CD4+CD25+Foxp3+T Cell Recruitment

Abstract: In order to know the effect of pre-existing Trichinella spiralis infection on experimentally induced intestinal inflammation and immune responses, we induced colitis in T. spiralis-infected mice and observed the severity of colitis and the levels of Th1, Th2, and regulatory cytokines and recruitment of CD4+CD25+Foxp3+ T (regulatory T; Treg) cells. Female C57BL/6 mice were infected with 250 muscle larvae; after 4 weeks, induction of experimental colitis was performed using 3% dextran sulfate sodium (DSS). Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 31 publications
0
24
0
1
Order By: Relevance
“…Schistosome infections, egg or adult worm extract suppressed Th1/17 responses and pathology and induced the Th2 cytokines IL-10 and TGF- β 3234 . Also, our previous study demonstrated that Trichinella spiralis infection derived T reg cells were the key cells mediating the amelioration of allergic airway inflammation and DSS-induced colitis in mice 35,36 . Infection with parasites such as Brugia malayi and Schistosoma mansoni triggers M2 macrophages 3741 .…”
Section: Introductionmentioning
confidence: 95%
“…Schistosome infections, egg or adult worm extract suppressed Th1/17 responses and pathology and induced the Th2 cytokines IL-10 and TGF- β 3234 . Also, our previous study demonstrated that Trichinella spiralis infection derived T reg cells were the key cells mediating the amelioration of allergic airway inflammation and DSS-induced colitis in mice 35,36 . Infection with parasites such as Brugia malayi and Schistosoma mansoni triggers M2 macrophages 3741 .…”
Section: Introductionmentioning
confidence: 95%
“…The occurrence of Treg cells was observed in both the spleen and peripheral lymph nodes, where CD4 + FoxP3 + , as well as CD8 + FoxP3 + cells, were increased [82]. The anti-inflammatory role of Tregs has been confirmed in experimental infections with Trichinella spiralis, where suppression of gut inflammation was related to the increased expression of IL-10 and TGF-β and expansion of Tregs [83]. Similarly, experimental infection with A. suum suppressed lipopolysaccharide (LPS)-induced inflammation in mice through mechanisms mediated by Tregs, regulatory IL-10 and TGF-β [84].…”
Section: Discussionmentioning
confidence: 87%
“…The role of Tregs in anti‐inflammatory activity has been demonstrated in other experimental infection models such as Trichinella spiralis . It was shown that mice infected with T. spiralis suppressed gut inflammation, and this suppression was associated with an increase in IL‐10 and TGF‐β and expansion of Treg cells . More recently, another group demonstrated that treatment of infected mice with E/S products of this worm showed similar profile with upregulation of Treg response and regulatory cytokines and downregulation of pro‐inflammatory cytokines …”
Section: Discussionmentioning
confidence: 97%